Synergistic improvement of the mechanical and biological performance of Si3N4 by incorporating nanostructured graphene - Zhe Zhan; Bin Deng; Yanru Chen; Xinghong Zhang; Jinzhu Song (Journal of Advanced Ceramics)
Achieving synergy between mechanical and biological performance has long been a challenge in developing silicon nitride (Si3N4) as a bone regeneration implant material. In this study, a nanostructured graphene-toughened Si3N4 composite (Si3N4–G) was prepared, and the mechanical and biological properties of the resulting Si3N4–G composite were compared with those of Si3N4 ceramics without graphene addition. The incorporation of nanostructured graphene substantially improves the mechanical properties of Si3N4. Furthermore, the nanoscale thickness of graphene enhances antibacterial activity through a “cutting” effect, while its high specific surface area promotes cell adhesion, activating mechanosensitive pathways linked to osteogenic differentiation. This work provides new insights into the potential applications of Si3N4-based bio-ceramics in bone tissue engineering.